Evaluasi Kinerja Organisasi Pengelola Zakat Berdasarkan PSAK 409 dan Sistem Pengendalian Internal (Studi Kasus pada BAZNAS Boyolali) - Luluk Ayuning Tyas; Sabrina Lailatul Khusna Arel; Rafa Ramadhani; Korniya Rohma Dhonis (Journal of Islamic Economics and Finance, 2026)
This study examines the transparency and performance of the zakat management organization (OPZ), its internal control system, oversight mechanisms, and zakat distribution methods at the National Zakat Agency (BAZNAS) in Boyolali Regency. A qualitative method was employed, with data collected through in-depth interviews, observations, and document analysis. Informants included OPZ managers, supervisors, and—the zakat beneficiaries. The study indicates that BAZNAS Boyolali has implemented transparency by preparing financial reports and publicizing its programs. OPZ performance can be considered good, as evidenced by improvements in collecting and distributing zakat funds. Oversight is conducted through internal and external means, such as audits and routine reports, although there is still room for improvement in the effectiveness of oversight. Zakat distribution is carried out in accordance with sharia principles and based on the needs of the mustahik. However, this distribution is not yet fully equitable and sustainable. Therefore, there is a need to improve transparency, strengthen internal controls, improve the oversight system, and innovate in zakat distribution methods to enhance public trust and the effectiveness of zakat management.